Deskripsi Kemampuan Pemecahan Masalah Matematika Berdasarkan Langkah Polya Ditinjau dari Gaya Berpikir Siswa pada Kelas VIII SMP Negeri 24 Makassar - Dassa, Awi; Djam'an, Nurwati; Iriana, Andi Irda (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This study is a descriptive study with qualitative approach which aimed to describe the mathematical problem solving abilities by Polya step terms of abstract sequential thinking style, concrete sequential, abstract random and concrete random. The subjects in this study are 4 (four) of students grade VIII SMPN 24 Makassar selected purposively based on the different of thinking style. Data collection tool is questionnaire to classify students based on the thinking style and to determine the subject, written tests and interviews to determine the ability of students' mathematical problem solving. Data were analyzed to describe the mathematical problem solving ability of students based on Polya steps namely; (1) understanding the problem, (2) devising a plan, (3) carrying out the plan and (4) looking back. The results showed that students' of premises concrete sequential and abstract random thinking styles has the same ability on the fourth problem solving step in understanding the problem, devising a plan, carrying out the plan and looking back on the process and results. While students with the type of abstract sequential thinking style and concrete random has a different problem solving steps on each of the four stages.